2023
DOI: 10.21203/rs.3.rs-3166569/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary composition plays a crucial role in the development of myopia through the inflammatory pathway: a Mendelian randomization study

Abstract: Background: Myopia is a major cause of global visual impairment, posing significant public health concerns, impacting daily lives, and leading to severe complications. Dietary factors may influence myopia development, while inflammation plays a role in various diseases and may contribute to myopia occurrence. This study aimed to investigate the impact of carbohydrate, protein, fat, and sugar intake on myopia using MR analysis. Additionally, we explored inflammation's potential role as a mediator. By elucidatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In particular, dietary salt restriction was ignored for decades as an effective and inexpensive treatment to reduce hypertension and to lower the effects of related ocular pathologies [13]. Moreover, as of 2023, "there are numerous conflicting findings, and no definitive consensus has been reached on the impact of diet on the occurrence and progression of myopia" [14]. For example, Chua et al found that dietary assessments of protein, fat, carbohydrate, and energy in Singaporean children were not associated with the development of myopia at three years of age [15] and nine years of age [16], yet dietary sodium is not mentioned in either study.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, dietary salt restriction was ignored for decades as an effective and inexpensive treatment to reduce hypertension and to lower the effects of related ocular pathologies [13]. Moreover, as of 2023, "there are numerous conflicting findings, and no definitive consensus has been reached on the impact of diet on the occurrence and progression of myopia" [14]. For example, Chua et al found that dietary assessments of protein, fat, carbohydrate, and energy in Singaporean children were not associated with the development of myopia at three years of age [15] and nine years of age [16], yet dietary sodium is not mentioned in either study.…”
Section: Introductionmentioning
confidence: 99%